Creation of OAIS-compliant archival packages for long-term preservation of regulatory metadata, records and dossiers - Stančić, Hrvoje (Array, 2012)
The authors continue their previous research on the long-term preservation solution for complex digital objects preserved as archival information packages in the domain of pharmaceutical records by evolving the proof of concept application "ArchiMed" to the level of the prototype. The research is put in the context of the responsibility of Marketing Authorisation Holders for submitting medicinal products’ dossiers to the National Competent Authorities, i.e., regulatory institutions, and the problems of long-term preservation of such records. The authors explain the problems those institutions are facing, the theory behind the long-term preservation concept and the requirements that digital preservation systems are facing with. The authors also explain the regulatory business process for better understanding of the organisational differences and technical issues on the European level. The differences between four formats of dossiers, NtA, CTD, NeeS and eCTD, are indicated. Based on the detected problems and previous proof of concept, the ArchiMed module was developed in order to further test its functionalities required by the digital preservation theory and to prove its conformance with the most important international standards like ISO 15489-1, ISO 14721: 2003 and others. The authors conclude that the proposed solution contributes to the regulation of archival procedures in the area of long-term preservation of regulatory records in the digital form. The paper shows how to regulate the regulatory process in the domain of control of medicines from the archival point of view with the aim of long-term preservation of important electronic records.